The stressed life of a lipid in the Zika virus membrane - Soñora, Martín; Barrera, Exequiel E.; Pantano, Sergio (Biochimica et biophysica acta. Biomembranes, 2022)
Protein-lipid interactions modulate a plethora of physiopathologic processes and have been the subject of countless studies. However, these kinds of interactions in the context of viral envelopes have remained relatively unexplored, partially because the intrinsically small dimensions of the molecular systems escape to the current resolution of experimental techniques. However, coarse-grained and multiscale simulations may fill that niche, providing nearly atomistic resolution at an affordable computational price. Here we use multiscale simulations to characterize the lipid-protein interactions in the envelope of the Zika Virus, a prominent member of the Flavivirus genus. Comparisons between the viral envelope and simpler molecular systems indicate that the viral membrane is under extreme pressures and asymmetric forces. Furthermore, the dense net of protein-protein contacts established by the envelope proteins creates poorly solvated regions that destabilize the external leaflet leading to a decoupled dynamics between both membrane layers. These findings lead to the idea that the Flaviviral membrane may store a significant amount of elastic energy, playing an active role in the membrane fusion process. [Display omitted] •Lipids in the Zika Virus envelope are exposed to extreme lateral pressures•The inner and outer leaflets of the viral envelope show decoupled dynamics, and different to those of flat membrane patches•The envelope in the mature virion stores tensile energy that may play an active role in membrane fusion